Avaliação de proposta estruturada na aprendizagem baseada em equipes (TBL Team-Based Learning) para utilização em um curso de Medicina - Oliveira, Carlos Alberto de (2014)
The aim in proposing this intervention was to use and evaluate the use of TBL as a methodology of teaching and learning in a medical school. The hypothesis that it was possible to replace the lectures in our universities, for TBL sessions with teacher training and student participatory interest in compliance with the National Curriculum Guide was present. The importance of the work is grounded in the mandatory changes that must occur in medical education, due to these recently approved guidelines; in the valuation of medical professionals prepared to working in multidisciplinary teams, committed to ethical and humanitarian care and, finally, the challenge of teaching in large rooms, with huge amounts of students, heterogeneous and in need of individualized formative assessments. The session was held in TBL in the format proposed by the TBL Collaborative Group (USA), during the theoretical supports of the second year. Prior to the sessions was distributed articles with the content of the lesson, fully contemplating the module objectives. In summary, we highlight that the average individual score was much lower than the average score of the team, with 99.999% reliability. The best individual performance was worse than the performance of their own team. The students demonstrated in their responses to the questionnaire, acceptability to the method. Teachers approved the activities highlighting not being able to apply the TBL sessions. After the study, we believe that this active methodology will provide students with better knowledge building, provided they are responsible with their preparedness